2021
DOI: 10.1155/2021/5522578
|View full text |Cite
|
Sign up to set email alerts
|

PCB118 Induces Inflammation of Islet Beta Cells via Activating ROS-NLRP3 Inflammasome Signaling

Abstract: Background. Diabetes mellitus is a clinical syndrome caused by genetic and environmental factors. Growing evidence suggests that exposure to environmental endocrine disruptors and activation of NLRP3 inflammasome signaling play a vital role in diabetes. However, it is unclear how PCB118, a common environmental endocrine disruptor, contributes to the incidence of diabetes, and its specific mechanism of action is unknown. In this study, we explored whether ROS-induced NLRP3 inflammasome priming and activation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In a mouse model, it was found that NLRP3i in pancreatic β cells could be activated by the environmental endocrine disruptor PCB118 via the oxidative stress pathway, leading to pancreatic β-cell inflammation. Increased levels of CCL-2, IL-1β, IL-6, IL-18, and caspase-1 were also observed in pancreatic β cells after PCB118 exposure [120]. It was observed that among diabetic subjects, a decrease in this inflammasome activity leads to an improvement in glycemic-related parameters and even prevents DM2 development by having protective effects on pancreatic β cells [121,122].…”
Section: Inflammation In the Pathogenesis Of Type 2 Diabetes Mellitusmentioning
confidence: 96%
“…In a mouse model, it was found that NLRP3i in pancreatic β cells could be activated by the environmental endocrine disruptor PCB118 via the oxidative stress pathway, leading to pancreatic β-cell inflammation. Increased levels of CCL-2, IL-1β, IL-6, IL-18, and caspase-1 were also observed in pancreatic β cells after PCB118 exposure [120]. It was observed that among diabetic subjects, a decrease in this inflammasome activity leads to an improvement in glycemic-related parameters and even prevents DM2 development by having protective effects on pancreatic β cells [121,122].…”
Section: Inflammation In the Pathogenesis Of Type 2 Diabetes Mellitusmentioning
confidence: 96%
“…Inflammatory cell infiltration was scored 0 -1 point if perivascular leukocyte count was 0; 1 point for perivascular leukocyte count of 2 -10; 2 points for perivascular leukocyte counts of 11 -20; 3 points for perivascular leukocyte counts of 21 -30, and 4 points for perivascular leukocyte counts in excess of 30 [11].…”
Section: Pathological Changes In Pancreatic Tissuementioning
confidence: 99%